Improvement of an alternative method for the correction of wall slip effects in rheological studies of filled rubber compounds (2024)
Developing new and improved rubber compounds to meet increasing demands for application specific product properties requires detailed knowledge of material properties to be able to predict the processing behavior. Therefore, rheological material properties, which are traditionally determined using the high-pressure capillary rheometer (HPCR) are of crucial importance. Rubber compounds often exhibit flow anomalies and non-isothermal effects, influenced by the compound ingredients and processing parameters that are generally neglected in rheological studies and simulations. This work presents an improved model for describing wall slip effects based on the Coulomb wall slip model, taking into account dissipative material heating. Rheological studies were performed on a carbon black-filled SBR tire tread compound. Using slit capillaries with different geometric dimensions, the pressure dependence of wall slip effects was confirmed, allowing the separation of the flow curve into wall adherent and wall slip regions.